2022
DOI: 10.1186/s42358-022-00234-7
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on COVID-19 vaccination in patients with immune-mediated rheumatic diseases: a Brazilian Society of Rheumatology task force

Abstract: Objective To provide guidelines on the coronavirus disease 2019 (COVID-19) vaccination in patients with immune-mediated rheumatic diseases (IMRD) to rheumatologists considering specific scenarios of the daily practice based on the shared-making decision (SMD) process. Methods A task force was constituted by 24 rheumatologists (panel members), with clinical and research expertise in immunizations and infectious diseases in immunocompromised patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
4
0
3
Order By: Relevance
“…Author details 1 Clinical Hospital, Federal University of Minas Gerais, Belo Horizonte, Brazil. 2 Lauro Wanderley Universitary Hospital, Federal University of Paraíba, R. Tab.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Author details 1 Clinical Hospital, Federal University of Minas Gerais, Belo Horizonte, Brazil. 2 Lauro Wanderley Universitary Hospital, Federal University of Paraíba, R. Tab.…”
Section: Abbreviationsmentioning
confidence: 99%
“…The Committee of Endemic and Infectious Diseases and the Executive Board of the Brazilian Society of Rheumatology (SBR) proposed an update to the “Guidelines on COVID-19 vaccination in patients with immune-mediated rheumatic diseases: a Brazilian Society of Rheumatology task force” [ 1 ] based on recently published scientific evidence [ 2 ] and on the new recommendations of the Brazilian National Immunization Program (NIP) for vaccination of immunocompromised persons [ 3 , 4 ]. According to the NIP documents [ 3 , 4 ], the primary vaccination series is composed of three doses of Coronavac or ChAdOx-1 (AstraZeneca) or mRNA BNT162b2 (Pfizer), or two doses of Ad26.COV2.S (Janssen).…”
mentioning
confidence: 99%
“…[36] Контроль ( 43) ГК (50) и др. у больных в целом (p<0,0001) и при лечении МТ (р=0,0017) E. Simader РА (53), mРНК МТ (55), ГИБП (51), Положительный АТ-ответ после первой и соавт. [37] СпА (46), ГК (22) из таблицы, ритуксимаб (РТМ), ГК, MT, абатацепт (АБЦ), микофенолата мофетил (ММФ) и иJAK ухудшают ответ на вакцину против SARS-CoV-2 у многих пациентов.…”
Section: обзорыunclassified
“…Несмотря на ряд нерешённых проблем, связанных с иммуногенностью и безопасностью вакцинации против SARS-CoV-2, эксперты всех международных и национальных ревматологических АНТИБИОТИКИ И ХИМИОТЕРАПИЯ, 2022, 67; 5-6 научных обществ [49,[52][53][54][55][56], включая Ассоциацию ревматологов России [57], поддерживают положение о том, что польза от вакцинации значительно превосходит потенциальный вред, связанный с развитием нежелательных явлений, поскольку вакцинация, несомненно, снижает риск инфицирования SARS-CoV-2 и тяжёлого течения COVID-19. Решение о проведении вакцинации против SARS-CoV-2 должно быть индивидуализированным, с учётом текущей эпидемической ситуации, активности ИВРЗ, характера проводимой терапии, основываться на достижении взаимопонимания между врачом и пациентом и происходить при обязательном подписании пациентом информированного согласия.…”
Section: рекомендации по вакцинацииunclassified
“…Some studies have shown a lower response in in this group of patients compared to healthy controls. It is unclear whether this is attributable to the underlying disease or its treatments [1].…”
Section: Introductionmentioning
confidence: 99%